THE DESCRIPTION OF SMOKING DEGREE BASED ON BRINKMAN INDEX IN PATIENTS WITH LUNG CANCER - Dessy Arumsari; Kurnia Dwi Artanti; Santi Martini; Sri Widati (Jurnal Berkala Epidemiologi, 2019)
Background: Smoking is a major risk factor that causes lung cancer. The high number of active smokers in developing countries is found in several countries; one of those countries is Indonesia. Purpose: The purpose of the study was to describe the degree of smoking based on brinkman index on lung cancer patients. Methods: It was a descriptive study. It employed cross sectional research design. The population in this study included lung cancer patients in Outpatient and Inpatient Dr. Soetomo Regional Public Hospital, Surabaya. The independent variable in this study was the degree of smoking. Whereas, the dependent variable in this study was lung cancer. Accidental sampling was used as the sampling technique of the study. The total sample were 31 respondents. The instrument used for collecting data was questionnaire containing the risk factors of lung cancer in November 2018. The categorization of smoking degrees used the Brinkman Index measurement. Data were processed by univariate analysis which was presented in the form of a frequency distribution table between variables. Results: Almost all of the respondents were on the age of > 40 years (90.30%) and male (96.80%). The majority of respondents were senior high school graduates (38.70%), and had other jobs (32.20%). Almost half of the respondents were classified into heavy smoking degree according to the brinkman index (48.40%). Conclusions: Some of cancer patients in Dr. Soetomo Regional Public Hospital Surabaya has a smoking degree of heavy category.